LEARNING MOTIVATION AND MATH ANXIETY IN RELATION TO MATHEMATICAL COMMUNICATION SKILLS OF HIGH SCHOOL STUDENTS - Risdani, Nia Ayumi; Miatun, Asih (Universitas Sembilanbelas November Kolaka, 2024)
The goal of this study was to ascertain how high school students' mathematical communication skills related to their learning motivation and math anxiety. In this study, a correlation approach to quantitative research methodology was employed. 192 students made up the sample, whereas 324 students made up the population. This investigation was carried out for grade X in the 2023/2024 academic year students at one of the public high schools in East Jakarta. Tests of mathematical communication skills and questionnaires on learning motivation and math anxiety were the tools employed. Multiple linear regression tests with the F and T tests were used to process this data. The finding of the research are (1) there wasÂ a simultaneously connection between learning motivation and math anxiety on mathematical communication skills, (2) there was a partial connection between learning motivation and mathematical communication skills, (3) there was no connection between math anxiety on mathematical communication skills.